Adverse Event Burden, Resource Use, and Costs Associated with Immunosuppressant Medications for the Treatment of Systemic Lupus Erythematosus: A Systematic Literature Review. (3rd April 2013) - Oglesby, A.; Shaul, A. J.; Pokora, T.; Paramore, C.; Cragin, L.; Dennis, G.; Narayanan, S.; Weinstein, A.
Abstract : This paper assessed the burden of adverse events (AEs) associated with azathioprine (AZA), cyclophosphamide (CYC), mycophenolate mofetil (MMF), methotrexate (MTX), and cyclosporine (CsA) in patients with systemic lupus erythematosus (SLE). Thirty-eight publications were included. Incidence of AEs ranged from 42.8% to 97.3%. Common AEs included infections (2.4–77%), gastrointestinal AEs (3.2–66.7%), and amenorrhea and/or ovarian complications (0–71%). More hematological cytopenias were associated with AZA (14 episodes) than MMF (2 episodes). CYC was associated with more infections than MMF (40–77% versus 12.5–32%, resp.) or AZA (17–77% versus 11–29%, resp.). Rates of hospitalized infections were similar between MMF and AZA patients, but higher for those taking CYC. There were more gynecological toxicities with CYC than MMF (32–36% versus 3.6–6%, resp.) or AZA (32–71% versus 8–18%, resp.). Discontinuation rates due to AEs were 0–44.4% across these medications. In summary, the incidence of AEs associated with SLE immunosuppressants was consistently high as reported in the literature; discontinuations due to these AEs were similar across treatments. Studies on the economic impact of these AEs were sparse and warrant further study. This paper highlights the need for more treatment options with better safety profiles.